Pengaruh Tontonan Platform Youtube Dalam Pemerolehan Bahasa Anak - Wresty Elsa Fitri (Lembaga Pengembangan Kinerja Dosen, 2023)
Language acquisition that occurs in children, apart from being influenced by the environment, can also refer to a spectacle. This research is sourced from the Youtube platform which is often used as an entertainment spectacle for children. Moreover, children under the age of now have a high curiosity. Once they introduce Youtube viewing, they will continue to use this social media as a means of entertainment. The acquisition that occurs in children can be seen from what he imitates in everyday spoken language. This research is a type of qualitative research that is descriptive by using the method of listening. The data from this study were conducted in the Tanjung Priok area, North Jakarta, namely on children aged five to six years. For the sake of creating language acquisition to achieve positive things, the family and the surrounding environment have an important role in the formation of children's language acquisition.